Don’t Give Up: A Case Study on Girls and Video Game Design (LEARNing Landscapes, 2013)
This case study examines the experience of two sixth grade girls who participated in a game-design class in a class taken by all students at their school. Questions were: How do the experiences observed demonstrate engagement with a story drawn from the participants’ own lives?; and: How does the experience observed reflect experiences leading to competency, perseverance and science, technology, engineering and math (STEM) self-efficacy and the development of interest in STEM careers? Findings were that the students were highly engaged with the chosen topic and demonstrated growth in the attribute of perseverance and self-efficacy in STEM skills.
Keywords: case study; technology; game design; girl; engagement; STEM; self-efficacy